Excess capacity and sustainable development in Java Sea fisheries - Squires, Dale; Omar, Ishak; Jeon, Yongil; Kirkley, James (Cambridge University Press, 2003)
Excess capacity and overfishing are problems in the open-access, common-pool fisheries-of the Java Sea. Data development analysis is used to estimate excess fishing capacity and the number of vessels to decommission in three Java Sea fisheries of Indonesia, the purse seine, mini purse seine, and longline. First- and second-best policy measures are discussed to reduce the excess capacity and give sustainable management and development. The importance of incentive design, asymmetric information, and the regulator's principal-agent problem are emphasized in license limitation programs.